SOLVING INDEFINITE INTEGRALS USING MAPLE SOFTWARE - Toshboeva Feruza Atamjanovna (PEDAGOGS, 2025)
Abstract: This article discusses methods for teaching the solution of indefinite integrals using the MAPLE software. Software tools help in understanding mathematical concepts more easily. With MAPLE’s user-friendly interface and powerful computational capabilities, the effectiveness of teaching students how to compute integrals can be enhanced. The article also provides practical examples of solving indefinite integrals in MAPLE. The integration of modern technologies and software into the educational process allows students to grasp mathematical theories more quickly and accurately. Using MAPLE facilitates the visualization of computation results, aiding students in better understanding various mathematical functions. This article provides a detailed analysis of the application of MAPLE in teaching indefinite integrals and its positive impact on the educational process.